(3GdMGTjI GdNdjdI Ydi YOI GdCUhds - (3GdbRhjfj, Ndjd Hf GdZGRj (B, (3J (B1089 (3g`s
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3aUd aj MbjbI GdcdGe hHjGf CbSGeg hLedI ef CMcGe hJQJjH GdCSeGA, gPG GdaUd GdQGHY ef aUhd GdcJGH hgh dHjGf GdeHGOF GddZhjI daf CUhd Gdabgs
(3BNQgG (B:s
(3BNQgG(B: (3hGdeQGO Cf cdG ef GdCbSGe GdePchQI aj Mce eG de jYQa MGdg ef GdCMcGe GdeLghdI GdJj de jQO NWGH aceG jMJGL ajgG Edi GdHjGf jMJGL ajeG fMf ajg Edjg(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 321s
(3GdPQjYI, L (B6: 108(3, L (B13: 223s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs